A study on the factors of organizational commitment that influence employee’s job stress / Sofiah Solehah Ismail - Ismail, Sofiah Solehah (2010)
Nowadays, there are a more number of researches about factors of employee’s job stress had been found. The purpose of this study is to identify significant between Organizational Commitment and employee’s job stress among employees around Seremban area. It is hope that the result derived from this study would enable organization to determine factors that contribute to employee’s job stress and to prevent the problem from being worse and can affect the productivity of the employee’s itself. The data was obtained by using two methods which are primary data and secondary data. For primary data, respondents were asked to answers 70 sets of questionnaires to determine the Level of Entrepreneurial Behavior. The Data then analyzed using Statistical Program for Social Science (SPSS) Program. The objective of this study is to determine the factors of the Organizational Commitment that influence Employee’s Job Stress. The result fro this study shows that the Normative Commitment have negative relationship towards the Employee’s Job stress, while the Affective Commitment and Continuance Commitment don’t show any relationship towards it. Through this study, it shows that Normative Commitment most influence employee’s job stress among workers in Seremban area.